1999
DOI: 10.1111/j.1095-8649.1999.tb00699.x
|View full text |Cite
|
Sign up to set email alerts
|

Diel feeding periodicity, daily ration and prey selectivity in juvenile brown trout in a subarctic river

Abstract: Feeding of age-1 brown trout Salmo trutta in a third-order river in northern Finland was usually highest in the twilight hours and lowest around midday. Diel periodicity in food intake was less distinct and rarely significant for age-0 trout. Daily rations declined seasonally, being lowest in October, and highest in June (age-1 trout) or early August (age-0 trout). Prey selection did not differ between day and night, but differences between age classes and sampling dates were distinct. Age-0 trout preferred Ep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
20
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 45 publications
1
20
0
Order By: Relevance
“…In summer, higher or different activity or movements are reported at night, dusk and dawn in streams (e.g. Jenkins 1969; Kreivi, Muotka, Huusko, Ma¨ki-Petays, Huhta & Meissner 1999;Young 1999;Diana, Hudson & Clark 2004;Ho¨jesjo¨, Ö kland, Sundstro¨m, Pettersson & Johnsson 2007). However, substantial opportunistic variation between individuals and for individuals over time appears common (Bunnell, Isely, Burrell & Van Lear 1998;Giroux, Ovidio, Philippart & Baras 2000;Ovidio et al 2002).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In summer, higher or different activity or movements are reported at night, dusk and dawn in streams (e.g. Jenkins 1969; Kreivi, Muotka, Huusko, Ma¨ki-Petays, Huhta & Meissner 1999;Young 1999;Diana, Hudson & Clark 2004;Ho¨jesjo¨, Ö kland, Sundstro¨m, Pettersson & Johnsson 2007). However, substantial opportunistic variation between individuals and for individuals over time appears common (Bunnell, Isely, Burrell & Van Lear 1998;Giroux, Ovidio, Philippart & Baras 2000;Ovidio et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Suggested causal mechanisms are linked to environmental heterogeneity, i.e. not only abiotic factors such as habitat (Young 1994;Ovidio et al 2002;Diana et al 2004), and water flow (Bunt, Cooke, Katopodis & McKinley 1999;Brown, Power & Beltaos 2001), light intensity (Clapp et al 1990;Young 1999;Ho¨jesjo¨et al 2007), and temperature (Clapp et al 1990;Young 1999), but also biotic factors (food availability and foraging tactics : Jenkins 1969;Clapp et al 1990;Kreivi et al 1999;Young 1999;Giroux et al 2000;Ovidio et al 2002;competition: Jenkins 1969;Ho¨jesjo¨et al 2007;anti-predator behaviour: Young 1999). In winter, studies of trout activity and movement patterns are even less consistent.…”
Section: Introductionmentioning
confidence: 99%
“…However, Amundsen, Bergersen, Huru, and Heggberget (1999) suggests that the studies that show a predominance of drift feeding did not properly allow opportunities for benthic foraging. Of the three salmonid species examined in this study, brown trout had previously been shown to be the most drift oriented feeder (Anderson et al, 2016;Kreivi et al,1999;Oscoz, Leunda, Campos, Escala, & Miranda, 2005). Moreover, during summer brown trout parr also exhibited a tendency for drift feeding in Grout Brook (Johnson & McKenna, 2015) which differs from a more benthic feeding strategy that we observed in Grout Brook in winter.…”
Section: Discussionmentioning
confidence: 86%
“…During nonwinter periods there has been considerable variation in the selectivity values that have been reported for several of the prey taxa consumed by brown trout in Grout Brook. Ephemerellids have usually been found to be positively selected (Sagar and Glova;Kreivi et al, 1999;Ruginis, 2008) while a single study reported them to be avoided (Sánchez-Hernández, Vieira-Lanero, Servia, & Cobo, 2011). Similarly, Sagar and Glova (1995) and Sánchez-Hernández et al (2011) found that chironomids were selected by brown trout but Kreivi et al (1999), Oscoz et al (2005 and Ruginis (2008) reported them to be avoided.…”
Section: Discussionmentioning
confidence: 99%
“…However, at the end of August, when juvenile salmon densities were at their highest, there is still 15 h of sunlight each day, and there is no complete darkness at night before the beginning of September. Other seasonal patterns in northern rivers are the peak in food availability; high food intake (Gibson et al, 1984;Huru, 1986;Erkinaro & Erkinaro, 1998;Kreivi et al, 1999;Amundsen et al, 2000) and the most intensive somatic growth (Erkinaro & Niemelä, 1995) of juvenile salmonids occurs in early summer. Active feeding is connected with strong territorial behaviour, which may result in low local densities of fish.…”
mentioning
confidence: 99%